Self and N2 collisional broadening of rovibrational lines in the ν6 band of methyl iodide (12CH3I) at room temperature: The J and K dependence. (July 2019) - Attafi, Y.; Hassen, A. Ben; Aroui, H.; Tchana, F. Kwabia; Manceron, L.; Doizi, D.; Auwera, J. Vander; Perrin, A.
Highlights: Fourier transform spectra of the ν6 band of methyl iodide (CH3 I). Measured self- and N2 -broadening coefficients for the ν6 band of CH3 I. Modeling of the J and K dependences. Abstract: Following our recent study devoted to measurements of intensities of rovibrational lines in the ν6 band of methyl iodide ( 12 CH3 I) centered at 892.918 cm − 1, room temperature infrared spectra of methyl iodide diluted in nitrogen at fourteen total pressures between 20 and 300 hPa have been recorded using the Fourier transform spectrometer Bruker IF125HR located at the LISA facility in Créteil. Three hundred and forty six N2 -broadening coefficients of methyl iodide rovibrational lines have been measured in the 824–951 cm − 1 spectral range using mono-spectrum non-linear least squares fitting of Voigt profiles. Pressure-induced line shifts were not needed to fit the spectra to the noise level and line mixing effects could be neglected. Six hundred and eight self-broadening coefficients have also been measured in the same spectral range using the pure methyl iodide spectra recorded in our previous work. The measured self-broadening coefficients range from 0.1460 to 0.3786 cm − 1  atm − 1 and the N2 -broadening coefficients range from 0.0723 to 0.1481  cm − 1  atm − 1 at 295 K. The average accuracy on the measured self- and N2 -broadening coefficients was estimated to 3%. Comparisons with measurements reported in the literature for the ν5 band of CH3 I shows a satisfactory agreement with average differences of 7% and 4% for the self- and N2 -broadening coefficients, respectively. The J and K rotational dependences of these coefficients have been observed and the latter modeled using an empirical polynomial expansion. On average, the empirical expression reproduces the measured self- and N2 -broadening coefficients to within 3% and 4%, respectively. The data obtained in the present work represent a significant contribution to the determination of broadening coefficients of CH3 I and complement the list of line positions and intensities generated in our previous work, thus providing useful spectroscopic information for atmospheric remote sensing and industrial detection of CH3 I. Graphical abstract: Image, graphical abstract